A Design and A Development of A Web Based Purchase Information System - Solikin, Mokhamad; Musyafa, Muhammad Akid; Yazid, Ahmad Subhan; Mulyanto, Agus (IJID (International Journal on Informatics for Development), 2013)
The desire to manage a company to move forward is always there and will almost certainly have become one of the planned long-term targets since founding the company. As more and more competition in the business world we need accurate information. Thus, the required information could be obtained by providing good data that will be processed in the transaction among supplier companies so that these operations are performed thoroughly, quickly and efficiently in accordance with the times. This research will be applied to CV. Barokah Abadi. Development methods used in building design of this system is waterfall method. Software to build this system is CodeIgniter, Xampp which there is PHP, MySQL as the database. This system can be used for data processing purchases of goods made by the company. So that transaction data processing is not done manually anymore. This system also uses the LAN in the processing of selling and buying. By which, it can use many separate computers perform the purchases, but the processes run from the same system so that transactions are quicker and more efficient.